Managing food security in Malaysia: a resource-based view (RBV) analysis - Zainol, Fakhrul Anwar; Wan Daud, Wan Norhayate; Abdullah, Zulhamri; Wan Yusoff, Wan Fauziah (Human Resource Management Academic Research Society, 2018)
This study was carried out in a case study approach with intended research focus of examining the impact of the intangible resources and tangible resources on the growth of the seed industry in Malaysia. The strategic management of food security in Malaysia became the main concern in this study. It is clear that food security has become an important focus and widely debated issue built on four dimensions; food availability, food stability, food accessibility and food utilization. In the Resource-Based view (RBV) perspective, the focus has been directed towards business start-up as a resource acquisition process, where the availability of unique resources is presumed to promote industry development.The findings revealed that a focus on both tangible and intangible resource development that includes, funds, land, technology, a skilled workforce, policy and brands reputation is likely to generate the most growth within the seed industry. In addition,firms with valuable resources stand a better chance of growth but due to some limitations, government supports are needed, particularly on intangible resources. The resource-based view (RBV) of the firm suggests that positive competitive outcomes are largely attributable to an organizations’ idiosyncratic resources. Hence, this study will help to link and identify the capabilities of both tangible and intangible resouces to fullfill RBV requirements in order to develop more effective support system for seed industry in Malaysia.